Patterns in the diversity of dragonflies (Odonata) in cities across Central Europe - Christoph WILLIGALLA; Thomas FARTMANN (European Journal of Entomology, 2012)
Urbanisation is an important cause of species extinctions. Although urban water systems are also highly modified, studies on aquatic or semi-aquatic organisms are rare. The aim of this study is to identify the factors that determine species richness of Odonata in 22 Central European cities and along an urban-rural gradient within six of them. With 64 indigenous species in total and an average of 33 species per city, the species richness of Odonata in Central European cities is comparatively high. A generalised linear model indicates that species richness is positively related to city area. Additional predictors are climatic variables (temperature amplitude, sunshine duration and July temperature) and the year last studied. Since most cities are usually located in areas with naturally high habitat heterogeneity, we assume that cities should be naturally rich in dragonflies. The role of city area as a surrogate for habitat and structural richness most likely explains why it is strongly associated with Odonata species richness. The relationship between species richness and the climatic variables probably reflects that Odonata species richness in Central Europe is limited by warm and sunny conditions more than by availability of water. The temporal effect (the year last studied) on species richness is likely to be a consequence of the recent increase in Mediterranean species associated with global warming. Urbanisation clearly has an adverse effect on the species diversity of Odonata. Species richness increases along a gradient from the centre of a city to the rural area and is significantly highest in rural areas. This pattern probably reflects a gradient of increasing habitat quality from the centre of cities to rural areas. Moreover, the number of water bodies is generally very low in the city centres. Based on our results, we make recommendations for increasing the abundance and number of species of dragonflies in cities.